Argumentasi Hadis Untuk Toleransi - Ismail Fahmi Arrauf Nasution; Miswari Miswari (Institut Agama Islam Negeri (IAIN) Salatiga, 2019)
This article has two tasks. First, explore the hadith which are the basis of Islamic arguments for religious tolerance. The second builds the hadith argument for tolerance. Researchers found in the popular hadith codification such as Shahih Bukhari and Shahih Muslim, explicitly difficult to find hadith tolerance. This problem is the basis of the building arguments for the perception that Islam does not teach tolerance, Islam is not a tolerant religion. Researchers find tolerance hadiths in popular codification more than the themes of mu’amalah and social relations. Tolerance hadiths are very much found in the theme of the faith. From tolerance traditions found to be able to roast the perception of Islam is not a tolerant religion. Researchers build Islamic arguments for tolerance based on tolerance traditions that have been collected. Researchers found that Islam is a religion that is peaceful and puts forward tolerant attitudes in religion and in social life. Islam as other religions is present as a religion that calls for good and forbids from bad attitudes and actions. Bad attitudes and actions arise from the selfhood of humans who come out of fitrah.